Robust cooperative positioning using DGPS and UWB for V2X applications - Gao, Yang (2017)
Road transportation injuries, environmental pollution, and traffic congestion have resulted in a considerable cost to society annually. They have led to an increasing demand for a new generation of Intelligent Transportation Systems (ITS) road applications, which promise to tackle these widespread issues. A common element of such applications is the positioning system, and its performance has been highlighted as one of the key enablers. With the rapid expansion of Global Navigation Satellite Systems (GNSS), satellite-based positioning and navigation will continue to be the predominant positioning solution for most of ITS road applications. GNSS positioning systems offer global coverage, they are primarily free of charge, operate in all weather conditions, and are available all day, every day. However, there are challenges for GNSS-based positioning for ITS applications; in particular, the limited availability and degraded performance of GNSS signals in urban canyons. These challenges could impede the adoption of ITS applications, such as collision avoidance systems, lane departure warning systems, connected and autonomous vehicles. There is a gap between the positioning performance of GNSS-based systems and the positioning performance demanded by ITS applications.